Proceedings of the MAAP-PAS-ANSO Hybrid Workshop on "Ecosystem Restoration: One-Health and Pandemics": Proceedings of the MAAP-PAS-ANSO Hybrid Workshop - Asiya Nawaz; Naveera Khan; Hanbal Ahmad; Irum Iqrar; Muhammad Ali; Zabta Khan Shinwari (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Humanity is currently dealing with a number of interlinked existential crises. Ecological degradation, climate change, and biodiversity loss have disastrous consequences for human health and well-being. Furthermore, the emergence and transmission of zoonotic diseases like COVID-19 are linked to ecosystem health. For example, zoonotic infections account for 75% of new infectious diseases, and they are mainly caused by unsustainable resource usage, animal factory farming, and other large-scale anthropogenic influences. As these pandemics show, environmental destruction can play an important role in a worldwide public-health crisis. It is commonly agreed that COVID-19 will not be the last pandemic. We need holistic approaches like One Health (an area of research that recognizes human, animal, and ecological health as interconnected). One health seeks to increase communication and collaboration between humans, animals, and environmental health professionals to prevent the spread of diseases. To shed light on this important topic, “Ecosystem Restoration: One-Health and Pandemics; hybrid workshop” was organized by the Pakistan Academy of Sciences (PAS) and Monbukagakhusho-MEXT Alumni Association of Pakistan (MAAP); and sponsored by the Pakistan Academy of Sciences (PAS) and Alliance of International Science Organization (ANSO) on June 5, 2022. More than 150 participants attended the hybrid workshop.